From optical pumping to electrical pumping: the threshold overestimation in metal halide perovskites. Issue 4 (15th February 2023) - Qin, Jiajun; Tang, Yang; Zhang, Jia; Shen, Tangyao; Karlsson, Max; Zhang, Tiankai; Cai, Weidong; Shi, Lei; Ni, Wei-Xin; Gao, Feng
Abstract : Estimation of the electrically pumped perovskite lasing threshold carrier density from conventional optical pumping is significantly overestimated due to the slow hot carrier cooling process. Abstract : The threshold carrier density, conventionally evaluated from optical pumping, is a key reference parameter towards electrically pumped lasers with the widely acknowledged assumption that optically excited charge carriers relax to the band edge through an ultrafast process. However, the characteristically slow carrier cooling in perovskites challenges this assumption. Here, we investigate the optical pumping of state-of-the-art bromide- and iodine-based perovskites. We find that the threshold decreases by one order of magnitude with decreasing excitation energy from 3.10 eV to 2.48 eV for methylammonium lead bromide perovskite (MAPbBr3 ), indicating that the low-energy photon excitation facilitates faster cooling and hence enables efficient carrier accumulation for population inversion. Our results are then interpreted due to the coupling of phonon scattering in connection with the band structure of perovskites. This effect is further verified in the two-photon pumping process, where the carriers relax to the band edge with a smaller difference in phonon momentum that speeds up the carrier cooling process. Furthermore, by extrapolating the optical pumping threshold to the band edge excitation as an analog of the electrical carrier injection to the perovskite, we obtain a critical threshold carrier density of ∼1.9 × 10 17 cm −3, which is one order of magnitude lower than that estimated from the conventional approach. Our work thus highlights the feasibility of metal halide perovskites for electrically pumped lasers.